(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Studying the thermal performance of residential buildings according to local data in terms of weather and dominant architectural and structural designs has become greatly required as a result of the large deficit in energy production (electricity) in Libya and to provide thermal comfort for housing occupants according to the requirements of international codes and to reduce energy consumption as much as possible without the use of mechanical equipment (passive design). This study investigated the thermal behavior of two different models that were collected from the study area (Al-Jufra region-Libya), the first plan with insulators and the second plan without insulators. Eight alternative cases of the two models were studied through Ecotect 2011 Autodesk software. The results showed a significant effect in energy consumption, in case of using different types of walls slabs and insulation systems with reduction in energy consumption up to 56% per unit of m2 which indicates the success of the insulation and the use of the most efficient structural elements in insulation. With more focus on the construction aspect